Sharifah food inventory management system - Tan, Yuan Jie (2022)
Sharifah Food is a food processing company that specialises in the ready meals market. Over the years, Sharifah Food had to manually take orders from its customer through WhatsApp and record the sales data in Excel sheets. Nevertheless, it was discovered that it became difficult to keep track of all sales, orders, and inventory as the company grew. Therefore, this project aims to implement a web-based computerised inventory management system that helps the company streamline the inventory management process. Moreover, the ecommerce platform will be built using the Progressive Web Application (PWA) to provide the customers with a quick and straightforward way to place orders. The basic functionalities of the inventory management system include product stock, promotional packages, orders, and discount management. On the other hand, the basic functionalities of the e-commerce platform include products and promotions browsing, viewing an item, adding to the shopping cart, search items, checkout and payments. The methodology adopted in this project is the Rapid Application Development (RAD) prototyping methodology, and the development process is divided into three main phases. After completing the system implementation, the systems were evaluated through unit, integration, system usability and user acceptance tests. The system usability and user acceptance tests were conducted remotely. The test results showed that the inventory management system and the e-commerce platform are easy to use and not complex. However, the users would require a little time to be familiar with the inventory management system. In conclusion, the project has achieved all the planned objectives and the systems were successfully developed and deployed.